Cationic carbon quantum dots derived from alginate for gene delivery: One-step synthesis and cellular uptake. (15th September 2016) - Zhou, Jie; Deng, Wenwen; Wang, Yan; Cao, Xia; Chen, Jingjing; Wang, Qiang; Xu, Wenqian; Du, Pan; Yu, Qingtong; Chen, Jiaxin; Spector, Myron; Yu, Jiangnan; et al.
Graphical abstract: Abstract: Carbon quantum dots (CQDs), unlike semiconductor quantum dots, possess fine biocompatibility, excellent upconversion properties, high photostability and low toxicity. Here, we report multifunctional CQDs which were developed using alginate, 3% hydrogen peroxide and double distilled water through a facile, eco-friendly and inexpensive one-step hydrothermal carbonization route. In this reaction, the alginate served as both the carbon source and the cationization agent. The resulting CQDs exhibited strong and stable fluorescence with water-dispersible and positively-charged properties which could serve as an excellent DNA condensation. As non-viral gene vector being used for the first time, the CQDs showed considerably high transfection efficiency (comparable to Lipofectamine2000 and significantly higher than PEI, p < 0.05) and negligible toxicity. The photoluminescence properties of CQDs also permitted easy tracking of the cellular-uptake. The findings showed that both caveolae- and clathrin-mediated endocytosis pathways were involved in the internalization process of CQDs/pDNA complexes. Taken together, the alginate-derived photoluminescent CQDs hold great potential in biomedical applications due to their dual role as efficient non-viral gene vectors and bioimaging probes. Statement of Significance: This manuscript describes a facile and simple one-step hydrothermal carbonization route for preparing optically tunable photoluminescent carbon quantum dots (CQDs) from a novel raw material, alginate. These CQDs enjoy low cytotoxicity, positive zeta potential, excellent ability to condense macromolecular DNA, and most importantly, notably high transfection efficiency. The interesting finding is that the negatively-charged alginate can convert into positively charged CQDs without adding any cationic reagents. The significance of this study is that the cationic carbon quantum dots play dual roles as both non-viral gene vectors and bioimaging probes at the same time, which are most desirable in many fields of applications such as gene therapy, drug delivery, and bioimaging.